Comparative Analysis of the Biochemical and Molecular Responses of Nannochloropsis gaditana to Nitrogen and Phosphorus Limitation: Phosphorus Limitation Enhances Carotenogenesis - Sun Young Kim; Hanbi Moon; Yong Min Kwon; Kyung Woo Kim; Jaoon Young Hwan Kim (Marine Drugs)
Nannochloropsis gaditana is well known for its potential for biofuel production due to its high lipid content. Numerous omics and biochemical studies have explored the overall molecular mechanisms underlying the responses of Nannochloropsis sp. to nutrient availability, primarily focusing on lipid metabolism. However, N. gaditana is able to synthesize other valuable products such as carotenoids, including violaxanthin, which has various biological functions and applications. In this study, we comparatively investigated the physiological, biochemical, and molecular responses of N. gaditana to nitrogen and phosphorus limitation, examining biomass production, photosynthetic activity, lipid, chlorophyll, and carotenoids content, and RNA-seq data. Nitrogen limitation decreased photosynthetic activity, chlorophyll content, and biomass production but increased lipid content. Phosphorus limitation substantially increased carotenoids content, with violaxanthin productivity of 10.24 mg/L, 3.38-fold greater than under the control condition, with little effect on biomass production or photosynthetic function. These results were generally consistent with the gene expression pattern observed in transcriptomic analysis. This integrated analysis shows that phosphorus limitation can be an economically competitive solution by enhancing valuable carotenoids while maintaining lipid and biomass production in N. gaditana.